Family Support in the Republic of North Macedonia - Irena Avirovic Bundalevska; Makedonka Radulovic; Angelka Keskinova (Проблеми на постмодерността, 2021)
Ensuring children's rights and family well-being is a priority of every European country. The Republic of North Macedonia, as a candidate country of the European Union, shares the same family values and family policies as the remaining EU member states. However, despite the past governmental efforts in the area of legal harmonization, several gaps have to be fulfilled and policies to be improved to achieve efficient institutions at the European level. To expand existing policies regarding family support, we consider crucial the analysis of the factual situation in the country, as a basic step towards further research. Therefore, this paper aims to initially provide an analysis of the family support legal framework of the country. Secondly, we intend to map governmental and non-governmental institutions in the Republic of North Macedonia which is responsible to provide family, children, and parents' support. By doing so, we can develop additionally omitted family policies or improve existing ones. Finally, the paper will present a list of competencies of the employees of family support institutions to evaluate more peculiarly their staff's skills standards.